Interaction of acylated and unacylated forms of E. coli alpha-hemolysin with lipid monolayers: a PM-IRRAS study - Vazquez, Romina Florencia (2017)
Uropathogenic strains of Escherichia coli produce virulence factors, such as the protein toxin alpha-hemolysin (HlyA), that enable the bacteria to colonize the host and establish an infection. HlyA is synthetized as a protoxin (ProHlyA) that is transformed into the active form in the bacterial cytosol by the covalent linkage of two fatty-acyl moieties to the polypeptide chain before the secretion of HlyA into the extracellular medium. The aim of this work was to investigate the effect of the fatty acylation of HlyA on protein conformation and protein-membrane interactions. Polarization-modulated infrared reflection-absorption spectroscopy (PM-IRRAS) experiments were performed at the air-water interface, and lipid monolayers mimicking the outer leaflet of red-blood-cell membranes were used as model systems for the study of protein-membrane interaction. According to surface-pressure measurements, incorporation of the acylated protein into the lipid films was faster than that of the nonacylated form. PM-IRRAS measurements revealed that the adsorption of the proteins to the lipid monolayers induced disorder in the lipid acyl chains and also changed the elastic properties of the films independently of protein acylation. No significant difference was observed between HlyA and ProHlyA in the interaction with the model lipid monolayers; but when these proteins became adsorbed on a bare air-water interface, they adopted different secondary structures. The assumption of the correct protein conformation at a hydrophobic-hydrophilic interface could constitute a critical condition for biologic activity.